The role of a museum‐based science education program in promoting content knowledge and science motivation. Issue 9 (8th June 2016) - Martin, Andrew J.; Durksen, Tracy L.; Williamson, Derek; Kiss, Julia; Ginns, Paul
Abstract: Informal learning settings such as museums have been identified as opportunities to enhance students' knowledge and motivation in science and to optimize the connection between science and everyday life. The present study assessed the role of a self‐paced science education program (situated in a medical science museum) in enhancing students' program‐related content knowledge, self‐efficacy, valuing, and aspirations. The study also investigated whether gains in content knowledge recall and motivation (as relevant to biology, anatomy, health) are associated with reported improvements in beliefs about health practices relevant to everyday life. The program aligned with a well‐established tripartite engagement framework conforming to cognitive, behavioral, and emotional engagement principles as well as principles underpinning guided discovery learning. Among a sample of N = 167 (upper) elementary and secondary school students (aged 10–16 years, M = 12.62 years), we found significant gains in content knowledge recall (achievement) and science motivation (self‐efficacy, valuing, aspirations) following participation in the science program. Additionally, gains in content knowledge recall and motivation were associated with reported improvements in beliefs about everyday health practices. © 2016 Wiley Periodicals, Inc. J Res Sci Teach 53: 1364–1384, 2016